(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This abstract discusses the safety rules that must be followed in atomic and nuclear laboratories. There are potential hazards when working with nuclear materials and radiation, so strict adherence to safety regulations is important in preventing accidents and ensuring safe work. The abstract covers such aspects as equipment maintenance and inspection, employee training, radiation detection and control systems, evacuation and emergency response procedures, and hazardous substances regulations.